2015
DOI: 10.14704/nq.2015.13.2.836
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Psychomanteum as a Psi-Conducive State of Consciousness

Abstract: The mirror gazing procedure termed the "psychomanteum" was developed by the world renowned psychiatrist Dr. Raymond Moody. It was designed to facilitate reunion experiences with deceased individuals, as a means of addressing the feelings surrounding bereavement. Although the modern psychomanteum is not normally employed to seek extra-sensory perception (ESP) information about the future, it may be that the psychomanteum is psi-conductive. For example, there are many similarities and differences between psychom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Radin and Rebman (1996) reported that power in different EEG frequency bands (i.e., beta, alpha, and theta) was correlated with changes in the magnetic field while participants were in the booth. In a controlled setup, Parra and Villanueva (2015) found evidence of psi-phenomena in the psychomanteum through purported telepathic communication indexed by mean scores, in relation to “hit pictures,” that exceeded the statistical probability of random responding. Nevertheless, results were inconclusive in enhancing ESP with respect to a comparison condition in which the mirror was covered with a blackboard.…”
Section: Resultsmentioning
confidence: 92%
“…Radin and Rebman (1996) reported that power in different EEG frequency bands (i.e., beta, alpha, and theta) was correlated with changes in the magnetic field while participants were in the booth. In a controlled setup, Parra and Villanueva (2015) found evidence of psi-phenomena in the psychomanteum through purported telepathic communication indexed by mean scores, in relation to “hit pictures,” that exceeded the statistical probability of random responding. Nevertheless, results were inconclusive in enhancing ESP with respect to a comparison condition in which the mirror was covered with a blackboard.…”
Section: Resultsmentioning
confidence: 92%
“…Studies included in previous meta-analyses that were then re-published after that meta-analysis, were not used in the present meta-analysis: for example, Holt (2007) = Holt (2013). If there was more than one version of the same study valid in the test period (using the same data), the more detailed study was used: thereby, Parra and Villanueva (2015) replaced two studies -i.e., Villanueva (2010, 2011); replaced Parra and Argibay (2013c). One study ordinarily valid in the test period (i.e., Parker, 2010) happened to include more accurate data from a study already used in a previous meta-analysis (i.e., Parker, 2006, which was therefore excluded from the present analysis -for details, see Storm, Tressoldi, & Utts, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…When that database (N = 29) was tested against our new database (N = 9), we found no significant differences: z scores, t(36) = 0.30, p = .768 (two-tailed); ES values, t(36) = 0.25, p = .801 (two-tailed). We combined the two databases (29 + 9 = 38), found no outliers, and thereby formed an updated homogeneous database of 38 studies collected for the period 1992 to 2018 -a 27-year span (actual publication dates were from 1997 to 2012): 7 mean z = 0.97 (SD = 1.27), 95%CI [0.549 to 1.381]; mean ES = 0.13 (SD = 0.19), 95%CI [0.071 to 0.194]. Neither of these CIs includes zero.…”
Section: Post Hoc Analyses Of Categoriesmentioning
confidence: 99%
See 2 more Smart Citations